Models of initiation fatigue crack paths proposed by Macha - Z. Marciniak; D. Rozumek (Fracture and Structural Integrity)
Professor E. Macha devoted his academic life to solving the problems connected with random multiaxial fatigue in components of machines and structures. In his studies he formulated stress, strain and energy criteria related to critical plane concept. He also proposed several methods to determine critical plane position. In particular, he formulated and verified weight functions applied in order to determine critical plane position. The variance method constituted another significant contribution to the development of methods for determining critical plane position. Apart from these criteria, Macha was exploring energy approach in fatigue of materials and the development of fatigue cracks. He has also observed that strain characteristics multiplied by stress amplitude determined at specimen half-life are applied to estimate fatigue life using energy criteria. However, for cyclically instable materials, stress amplitude value may differ a lot; therefore he proposed the method to determine energy fatigue characteristics directly from experimental research.